TN

Chứng minh 2x + y + y2 = (1 - xy + y).(2x + y) + xy(2x + y - 2)

NT
11 tháng 8 2024 lúc 10:57

\(\left(1-xy+y\right)\left(2x+y\right)+xy\left(2x+y-2\right)\)

\(=2x+y-2x^2y-xy^2+2xy+y^2+2x^2y+xy^2-2xy\)

\(=2x+y+y^2\)

Bình luận (0)
T1
11 tháng 8 2024 lúc 10:59

Ta có \(VP = ( 1 - xy + y) .(2x +y) + xy (2x + y -2)\)

 =  \(2x + y - 2x^{2}y - xy^{2} + 2xy + y^{2} + 2x^{2}y + xy^{2} - 2xy\)

\(2x + y ^{2} + y = VT\)

Bình luận (0)

Các câu hỏi tương tự
TT
Xem chi tiết
NP
Xem chi tiết
PB
Xem chi tiết
NS
Xem chi tiết
TA
Xem chi tiết
H24
Xem chi tiết
VH
Xem chi tiết
VC
Xem chi tiết
NT
Xem chi tiết
HM
Xem chi tiết